2009
DOI: 10.2337/dc08-2143
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in the Early Stage of Type 2 Diabetes

Abstract: OBJECTIVEType 2 diabetes is known to be associated with decrements in memory and executive functions and information-processing speed. It is less clear, however, at which stage of diabetes these cognitive decrements develop and how they progress over time. In this study, we investigated cognitive functioning of patients with recent screen-detected type 2 diabetes, thus providing insight into the nature and severity of cognitive decrements in the early stage of the disease. Possible risk factors were also addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
138
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(155 citation statements)
references
References 23 publications
12
138
1
4
Order By: Relevance
“…There was no significant positive correlation (p>0.05) between sex of patients and cognitive dysfunction in our study which is consistent with a previous syudy by Ruis et al (2009) Our study did not show any significant positive correlation (p>0.05) between dyslipidemia and BMI with cognitive dysfunction which was also observed in other studies.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…There was no significant positive correlation (p>0.05) between sex of patients and cognitive dysfunction in our study which is consistent with a previous syudy by Ruis et al (2009) Our study did not show any significant positive correlation (p>0.05) between dyslipidemia and BMI with cognitive dysfunction which was also observed in other studies.…”
Section: Discussionsupporting
confidence: 83%
“…Ruis et al (2009) had shown that diabetes duration was associated with the effect size (cognitive decline) of the study: the longer the known diabetes duration, the bigger the effect size which was substantiated by other studies. In the Study of Osteoporotic Fractures (Gregg et al, 2000), there was a trend of increasing risk of cognitive decline with increasing duration of diabetes, and in the Framingham study (Elias et al, 1997), each 5-year increment between diabetes diagnosis and cognitive assessment was associated with lower scores on tests of logical memory, word fluency, and similarities.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Additionally, lower premorbid intelligence has been frequently reported in DM2 individuals (7,31), thus lower intelligence is an integral part of this condition which may in fact account for some of the cognitive deficits observed. Indeed, low intelligence is considered a risk factor for DM2 and a range of other chronic conditions, possibly in part because such individuals may be more inclined to engage in adverse health behaviours that increase the risk of disease (32).…”
Section: Discussionmentioning
confidence: 97%